2008
DOI: 10.1177/0165025407087211
|View full text |Cite
|
Sign up to set email alerts
|

Children in Asian cultures say yes to yes—no questions: Common and cultural differences between Vietnamese and Japanese children

Abstract: We investigated whether children's response tendency toward yes-no questions concerning objects is a common phenomenon regardless of languages and cultures. Vietnamese and Japanese 2- to 5-year-old (N = 108) were investigated. We also examined whether familiarity with the questioning issue has any effect on Asian children's yes bias. As the result, Asian children showed a yes bias to yes-no questions. The children's response tendency changes dramatically with their age: Vietnamese and Japanese 2- and 3-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
49
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 19 publications
(19 reference statements)
14
49
4
Order By: Relevance
“…We also found that the 6-year-olds in this study exhibited a nay-saying bias to unfamiliar objects, as did Japanese 5-year-olds in Okanda and Itakura's (2008) study, but Okanda and Itakura (2010b) and Okanda and colleagues (2011) did not find such biases in Japanese 5-and 6-year-olds. These inconsistent results within a country suggest that in addition to cultural factors (Okanda & Itakura, 2010b), other factors such as the social relationship between a questioner and a respondent might influence response biases in older preschoolers.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…We also found that the 6-year-olds in this study exhibited a nay-saying bias to unfamiliar objects, as did Japanese 5-year-olds in Okanda and Itakura's (2008) study, but Okanda and Itakura (2010b) and Okanda and colleagues (2011) did not find such biases in Japanese 5-and 6-year-olds. These inconsistent results within a country suggest that in addition to cultural factors (Okanda & Itakura, 2010b), other factors such as the social relationship between a questioner and a respondent might influence response biases in older preschoolers.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, unlike the children in Okanda and Itakura's (2008) study, the children in this study did not produce a large number of ''I don't know'' and ''no answer'' responses; however, it might be premature to draw conclusions without testing Asian children with incomprehensible questions.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Gardiner, Harris, Ohmoto, and Hamazaki (1988) reported that a number of Japanese preschool children fell silent during developmental psychological experiments in which they were told some stories and then asked to answer questions about the protagonist's emotions. Also, Okanda and Itakura (2008) found that Japanese children may have stronger response biases than Western and Vietnamese children when asked questions by an interviewer. For example, Japanese preschool children are more likely to answer "yes" when given yes-no questions, and, sometimes, not to respond to the interviewer's questions.…”
mentioning
confidence: 99%